2014
DOI: 10.1155/2014/790473
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical Properties of Nano‐ and Microsized Crystals in the Urine of Calcium Oxalate Stone Patients and Control Subjects

Abstract: Purpose. To compare the properties of different sizes of urinary crystallites between calcium oxalate (CaOx) calculi patients and healthy controls. Methods. We studied the average particle size, size distribution, intensity-autocorrelation curve, zeta potential ( ), conductivity, mobility, aggregation state, and stability of different sizes of urinary crystallites by nanoparticle size analysis and transmission electron microscopy after filtration through a microporous membrane with an aperture size from 0.22 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…On the other hand, random distribution of the uric acid crystallites observed in the CARS images suggests that they adhered to the already formed stones in the urinary tract. Solubility of uric acid in water is low, and, subsequently, uric acid microcrystallites may be present in urine of even healthy humans . During formation of stones in urinary tract, the crystallites might be incorporated into the stones' structure.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, random distribution of the uric acid crystallites observed in the CARS images suggests that they adhered to the already formed stones in the urinary tract. Solubility of uric acid in water is low, and, subsequently, uric acid microcrystallites may be present in urine of even healthy humans . During formation of stones in urinary tract, the crystallites might be incorporated into the stones' structure.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal size may also be an important factor in cell injury, as recent studies have shown that CaOx nanocrystals cause more cytotoxic effects than microcrystals on renal epithelial cells. 25 Furthermore, nano-scaled crystallites isolated from CaOx stone formers have been shown to more 27 Thus, the ability to accurately detect nanocrystals in the urine could be a useful tool for identifying factors associated with crystal agglomeration and crystal toxicity, and for understanding and managing kidney stone disease. Few studies have detected nanocrystals in the urine using a nanoparticle analyzer and nano-flow cytometer.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have detected nanocrystals in the urine using a nanoparticle analyzer and nano-flow cytometer. 14,27,28 These methods required labeling crystals with fluorescent probes and dyes for visualization under the microscope or flow cytometry. 28,50 Their findings suggested nanocrystals could be important to understand stone pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Что касается витамина С, то его употребление в сутки с продуктами и лекарственными средствами не должно превышать 150-200 мг, поскольку при избыточном употреблении этого витамина растет образование ЩК [35,43,44].…”
Section: диета при обменных нефропатияхunclassified